Історія введення в культуру та використання Morus alba L. - Vitenko, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The history of introduction of Morus alba L. in Ukraine has been presented. It was determined that Morus alba is the perspective plant for the planting of greenery and medicine.